Facial Identification at a Virtual Reality Airport. (July 2019) - Tummon, Hannah M.; Allen, John; Bindemann, Markus
Person identification at airports requires the comparison of a passport photograph with its bearer. In psychology, this process is typically studied with static pairs of face photographs that require identity-match (same person shown) versus mismatch (two different people) decisions, but this approach provides a limited proxy for studying how environment and social interaction factors affect this task. In this study, we explore the feasibility of virtual reality (VR) as a solution to this problem, by examining the identity matching of avatars in a VR airport. We show that facial photographs of real people can be rendered into VR avatars in a manner that preserves image and identity information (Experiments 1 to 3). We then show that identity matching of avatar pairs reflects similar cognitive processes to the matching of face photographs (Experiments 4 and 5). This pattern holds when avatar matching is assessed in a VR airport (Experiments 6 and 7). These findings demonstrate the feasibility of VR as a new method for investigating face matching in complex environments.